Effect Handlers in Haskell, Evidently - Xie, Ningning; Leijen, Daan (The 13th ACM SIGPLAN International Haskell Symposium, 2020)
Algebraic effect handlers offer an alternative to monads to incorporate effects in Haskell. In recent work Xie _et al._ show how to give semantics to effect handlers in terms of plain polymorphic lambda calculus through _evidence translation_. Besides giving precise semantics, this translation also allows for potentially more efficient implementations. Here we present the first implementation of this technique as a library for effect handlers in Haskell. We show how the design naturally leads to a concise effect interface and how evidence translation enables evaluating _tail resumptive_ operations _in-place_. We give detailed benchmark results where our library performs well with respect to other approaches.